THE ISSUE OF SOVEREIGNTY AND THE IDEA OF PATRIOTISM IN THE WRITINGS OF ALGERIAN HISTORIANS 1830-1962 - benazouaou, Fath al-Din (The Algerian Historical Journal, 2026)
This research aims to discover the position of some Algerian historians on the issue of sovereignty and the idea of patriotism in Algeria, it examines the historical facts and the scientific arguments presented and the methodology adopted in these historians’ study of these two issues, in the course of their various responses to the fallacies of the colonial historical school in this field, through the writings of some pioneers of the first generation of historians (Khodja, El Mili, El Madani), and the literature of the second generation (Saâdallah, Zoubairi, Saidouni, Bouaziz, Genan ...). The research resulted in a set of results, centered around the importance of the new scientific proposal for Algerian historians, in which they exposed the falsity of the theses of the colonial school of history, and formulated a scientific and intellectual trend, which has become a reference for many scientific researches, and a basis for many cultural and political discussions in Algeria.